2021
DOI: 10.1007/s10803-021-05244-w
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Children and Adolescents with Autism, ADHD and Co-occurring Autism and ADHD, During Passive and Active Experimental Conditions

Abstract: Despite overlaps in clinical symptomatology, autism and ADHD may be associated with opposite autonomic arousal profiles which might partly explain altered cognitive and global functioning. We investigated autonomic arousal in 106 children/adolescents with autism, ADHD, co-occurring autism/ADHD, and neurotypical controls. Heart rate variability was recorded during resting-state, a ‘passive’ auditory oddball task and an ‘active’ response conflict task. Autistic children showed hyper-arousal during the active tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…To establish a reliable basis and objective diagnosis of ASD and ADHD previous studies have analyzed different biosignals such as electroencephalogram (EEG) [11], [12], heart rate variability (HRV) [13], and eye tracking [14]. Shephard et al has reported reduced power in alpha and theta bands in ASD subjects whereas ADHD subjects exhibited decreased power in delta bands of the EEG [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To establish a reliable basis and objective diagnosis of ASD and ADHD previous studies have analyzed different biosignals such as electroencephalogram (EEG) [11], [12], heart rate variability (HRV) [13], and eye tracking [14]. Shephard et al has reported reduced power in alpha and theta bands in ASD subjects whereas ADHD subjects exhibited decreased power in delta bands of the EEG [12].…”
Section: Introductionmentioning
confidence: 99%
“…Shephard et al has reported reduced power in alpha and theta bands in ASD subjects whereas ADHD subjects exhibited decreased power in delta bands of the EEG [12]. Bellato et al showed atypical autonomous response obtained from HRV as an indicator to separate ASD and ADHD with reduced parasympathetic activation in ASD during stress and reduced sympathetic functioning in ADHD during resting [13]. These studies based on EEG and HRV did not report any quantification of classification performance and were limited to statistical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 describes potential objective, physiological diagnostic tests for emotional dysregulation, sensory dysregulation, and attentional dysregulation found in ADHD. The pupil reflex test, correlates pupil constriction and subsequent dilation in response to light to attentional dysregulation (Wainstein et al, 2017) and autonomic dysfunction (Hamrakova et al, 2019(Hamrakova et al, , 2020Bellato et al, 2021) in ADHD. Additionally, if we further explore the relation between emotional and sensory dysregulation and the classical ADHD symptoms, more potential diagnostic practices may arise.…”
Section: Discussionmentioning
confidence: 99%
“…Altered synchronization of oscillatory activity in ASD has been found across paradigms and has been linked to abnormal perception and performance 26,84 . A separate set of evidence points to altered autonomic activity, with hypo-and hyper regulation of pupillometry, cardiac and electrodermal activity 85,86 . Despite this evidence, autonomic system and brain processes have not been considered in unison, or systematically in different environmental scenarios, in ASD.…”
Section: Discussionmentioning
confidence: 99%